(untitled) (The Pakistan Development Review, 1974)
The family is one of the basic social institutions of human society. The behaviour of individuals is to a great extent moulded by influences within the family not only during the socialization process at early ages, but also after they have reached maturity. The way in which the family system operates has important demographic consequences. Reproduction takes place within the family, and fertility is affected by the combination of events occurring within and shaped by the prevailing family system in a society. The family is an important decision-making unit, and in societies where the extended family system1 is prevalent, decisions by couples regarding fertility behaviour may be strongly influenced by the larger family network. Hill [11, p. 271-72] has identified some crucial decisions made over the reproductive career of a couple. He suggests that these decisions are largely influenced by the parents and other relatives concerning (a) when to marry, (b) how soon to have first child, (c) whether to use birth control and method to be used, (d) when to have second and later children, and (e) when to stop child bearing. Davis and Blake [4] point out certain intermediate variables which an individual learns during the sociali¬zation process, e.g., acceptability of universal marriage, permissibility of sexual abstinence, the long absence of either spouse and the frequency and timing of sexual intercourse, etc. All of these have direct bearing on fertility in the long run.